Pembelajaran Masyarakat dan Peningkatan Literasi Digital: Model Terbaik untuk Pemberdayaan Ekonomi Lokal - Rangga Saputra; Aidil Adoha Dly; Gusmaneli (Jurnal Ekonomi dan Bisnis Digital, 2024)
Digital literacy plays a crucial role in local economic empowerment by enhancing community skills and knowledge in utilizing information technology. Through digital literacy, communities can access information, collaborate, and innovate, which in turn increases competitiveness and sustainability of the local economy. Community-based learning is an effective approach to enhance digital literacy, as it allows active community participation and adapts learning materials to local needs. Thus, digital literacy not only contributes to improving quality of life but also strengthens economic resilience in facing global challenges. Efforts to enhance digital literacy among communities are essential steps in promoting sustainable local economic empowerment.